Status quo and predictors of Weibo users’ attitudes toward lesbians and gay men in 31 provinces in the Chinese mainland: Analysis based on supervised machine learning and provincial panel data - Zheng, Quan; Guo, Ying; Wang, Zhen; Andrasik, Frank; Kuang, Ziyi; Xu, Sheng; Hu, Xiangen (Frontiers in Psychology, 2023)
Public attitudes toward consensual same-sex relations are crucial to lesbians’ and gay men’s rights and society’s well-being, but research addressing this topic in China is limited. We comprehensively explored the current status and predictors of Weibo users’ attitudes toward individuals who are lesbian or gay (IWLG) at the provincial level in the Chinese mainland. Natural language processing and machine learning techniques were incorporated to analyze 1,934,008 Weibo posts from January 1, 2010, to December 31, 2020, to evaluate Weibo users’ expressed attitudes toward IWLG in 31 provinces in the Chinese mainland guided by the ABC Model of attitude. Although Weibo users from different provinces are generally supportive and accepting of people who are gay and the rights of the gay community, considerable misconceptions and inaccurate knowledge of IWLG surfaced in Weibo users’ posts. Economic development and educational level were important predictors of specific attitudes toward IWLG at the provincial level. Increased efforts to address the unbalanced and insufficient development between different provinces could help reduce the public’s prejudice, stigma, and discrimination toward IWLG. Policies that facilitate greater implementation of Comprehensive Sexuality Education sequentially and effectively are suggested as well.